2022
DOI: 10.1002/anie.202207175
|View full text |Cite
|
Sign up to set email alerts
|

Novel Poxin Stable cGAMP‐Derivatives Are Remarkable STING Agonists

Abstract: 2',3'-cGAMP is a cyclic A-and G-containing dinucleotide second messenger, which is formed upon cellular recognition of foreign cytosolic DNA as part of the innate immune response. The molecule binds to the adaptor protein STING, which induces an immune response characterized by the production of type I interferons and cytokines. The development of STINGbinding molecules with both agonistic as well as antagonistic properties is currently of tremendous interest to induce or enhance antitumor or antiviral immunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…also disclosed that such 2’ deoxy/hydrogen, fluoro and methoxy c‐di‐AMP mimics could inhibit and reduce the degradation of c‐di‐AMP by GdpP, a PDE in Listeria monocytogenes [34] . Similarly, 2’ fluorinated carbocyclic and deoxy ribose modified 2’3’‐cGAMP analogs have recently been shown as poxin‐resistant STING agonist [35,36] . Poxin readily cleaves 2’3’‐cGAMP; the 2’OH is required for poxin degradation of 2’3’‐cGAMP [24] .…”
Section: Resultsmentioning
confidence: 99%
“…also disclosed that such 2’ deoxy/hydrogen, fluoro and methoxy c‐di‐AMP mimics could inhibit and reduce the degradation of c‐di‐AMP by GdpP, a PDE in Listeria monocytogenes [34] . Similarly, 2’ fluorinated carbocyclic and deoxy ribose modified 2’3’‐cGAMP analogs have recently been shown as poxin‐resistant STING agonist [35,36] . Poxin readily cleaves 2’3’‐cGAMP; the 2’OH is required for poxin degradation of 2’3’‐cGAMP [24] .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, our aim was to prepare cGAMP analogs that would be resistant against the viral endonuclease poxin, which specifically cleaves cGAMP. So far only few analogs of cGAMP, phosphorothioate and dideoxy cGAMP, were described as poxin resistant [10,12]. The ribose 2'hydroxyl group is essential for poxin mediated cleavage of cGAMP.…”
Section: Disccussionmentioning
confidence: 99%
“…Recently, the Carell team observed that dideoxy-2′,3′-cGAMP and its derivatives, characterized by the absence of secondary ribose-OH groups, constitute a class of STING agonists that demonstrate stability against poxins [12]. We have prepared a novel class of fluorinated cyclic dinucleotides that exhibit high potency against STING and are not cleavable by poxin.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of this mechanism, Stazzoni et al rationally designed dideoxy 2′3′cGAMP ( 4 ) lacking the 2′OH and showed that this 2′3′cGAMP analogue exhibited resistance to poxin cleavage while maintaining STING agonism. 29 A few groups have also reported hydrolytically stable phosphorothioate 2′3′cGAMP analogues, such as 2 , 3 and 5 (Fig. 1), which are now in various stages of clinical trials as a cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%